The applicability of anaerobically digested pasteurized pit latrine faecal sludge as a fertilizer to grow radish and garden cress - Madikizela, Phindile (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Pit latrine faecal sludge was recovered from numerous pit latrines in Hlalani Township, Grahamstown, South Africa. This material was used to prepare a fertilizer to demonstrate the value that could be captured from faecal sludge. Further anaerobic digestion, together with a co-feed demonstrated the potential of faecal sludge to produce low cost fertilizer that could be used to grow food crops. Biogas recovered from the anaerobic digester could be used to pasteurize its effluent, although effective biogas recovery and storage needs to be further addressed. Investigating the microbial community of the different depths of the pit latrine through molecular techniques showed that the fermenting bacteria family Clostridiaceae was the most commonly identified family throughout the different depths of the pit latrine, and that the microbial community within pit latrines was very diverse with bacterial families that are involved in nitrogen fixation, denitrification, and iron and sulphate reduction. Additionally, most of the bacterial families that dominated the seven studied pit latrines had members that were known human pathogens (Mycobacteriaceae, Dermatophilaceae Peptostreptococcaceae, Micrococcaceae, Staphylococcaceae, Leptospiraceae, Listeriaceae, Bradyrhizobiaceae and Brucellaceae). Effluent from a wastewater treatment works was selected as a co-feed to augment biogas production. The most successful faecal sludge and co-feed combination was shown to be the one made up of 33% and 66% pit latrine faecal sludge. 180 L of this effluent mixture generated 285 L of biogas over 45 days of anaerobic digestion (29±2°C). However, the recovered quantities were insufficient for pasteurization as 650 L of biogas was required to pasteurize 300 g of faecal sludge for 1 hour at 70±2°C. Therefore, liquid petroleum gas (LPG) was used as an alternative heating energy source. Anaerobic digestion and pasteurization rendered the faecal sludge safe for application as a fertilizer as the quality of the faecal sludge after treatment by anaerobic digestion and pasteurization was within the microbiological (Escherichia coli, Salmonella spp, Enterococcus faecium and helminth eggs) and trace element restrictions (Pb, Ni, Cr, Mo, As, Cu, Mn, Fe, Cd and Hg) of sludge application in agriculture as stipulated by the WHO and the South African Guidelines for Sludge Use in Agriculture. Radish (Raphanus sativus spp) and garden cress (Lepidium sativum) were cultivated to demonstrate the effectiveness of the anaerobically digested and pasteurized pit latrine faecal sludge as a fertilizer. Diluting the fertilizer prepared from faecal sludge did not reduce its efficacy and was comparable to the synthetic fertilizer used as a control in the growth trials in terms of the plant fresh weight, dry weight and plant height. Finally, the exposure to the current state of pit latrines in Hlalani Township provided an incentive to develop a new tool to address sanitation service delivery skill shortage (artisans, plant operation and maintenance workers, and sanitation and hygiene facilitators) through the use of volunteers.
Keywords: Sewage sludge as fertilizer; Sewage sludge digestion; Sewage -- Purification -- Anaerobic treatment